O triptofano agrava o comportamento tipo-depressivo induzido por encefalopatia associada à sepse em roedores - Rosa, Eduardo Augusto Alves (2023)
Depressive disorder is characterized by episodes of depressed mood, loss of interest and pleasure. Animal models are quite convenient in studying the pathophysiology of depressive disorders. This work aimed to characterize a study animal model for depressive disorders through the bias of inflammation, based on surgical interventions of cecal ligation and perforation (CLP), aiming at the therapeutic intervention of supplementation with tryptophan. To do so, initially, we performed behavioral tests of forced swimming (which assesses motivation), sucrose preference (assessing anhedonia) and open field (to analyze locomotion) on the 7th, 14th and 21st day after the simulation (Sham) or sepsis induction (CLP), with the aim of defining the best period for supplementation. The CLP group showed a depressivelike behavior on the 7th and 14th days, evidenced by the reduction of swimming time and increase of immobility time compared to the control group. Through the analysis of the data from the open field test, we observed that the surgery did not interfere with the locomotion of the animals. Subsequently, another group of animals received supplementation with tryptophan (10 or 100 mg/Kg) or vehicle, for 7 consecutive days, between the 7th and 14th day after the surgical procedure. On the 14th day, the animals were submitted to the previously mentioned behavioral tests. In the analyzes of behavioral tests, we observed that tryptophan supplementation was able to aggravate depression-like behavior in rodents. Thus, we hypothesized that tryptophan was absorbed through the kynurenine pathway, not being a serotonin precursor in cases of chronic inflammation.